Islamist terrorism and democracy in the Middle East - Dalacoura, Katerina (Cambridge University Press, 2011)
Through detailed research into the activities of both radical and moderate organizations across the Middle East, such as the Muslim Brotherhood, Hamas and Hizbullah, and via interviews with key personnel, Katerina Dalacoura investigates whether repression and political exclusion pushed Islamist entities to adopt terrorist tactics.